Immersive histories: : Photography and The Absorption of the Past (International Journal on Stereo & Immersive Media, 2021)
Photographs create a saturating awareness of the past in public spaces, notably the street and the open-air as sensorially immersive spaces. I considered how photographs operate as an unintentional encounter with, and immersion in, the past, generating a low-level sense of the value of that past. Departing from technologies of immersion in the usual sense, and from self-conscious and intentional engagements with the visual, I draw on ideas of non-cognitive awareness and the fugitive practices that exist in the dynamics of susceptibility at the interstices of everyday life.  I consider how, since the nineteenth century, and into the digital age, photographs have created historically-scripted spaces and an immersive sense of historical connection and continuity, creating an intensification of historical imagination and coherence of sentiment. In this, the immediacy of photographs is used to create banal, folded presences of the past, a historical ‘habitus’ which intensifies the space-time of the street.